Examining the Halal Perspective of Pre-Order Transactions in Gold Buying and Selling: A Qualitative Descriptive Analysis - Rizali, Muhammad; Pajriah, Rihani (PT. Sharia Journal and Education Center, 2024)
Abstract This research will discuss buying and selling, especially buying and selling gold. Gold today is not only favored as a woman's jewelry but as a means of investment. The existence of gold buying and selling transactions by pre order raises questions that develop in the community regarding the halal and haram laws. This research is a type of qualitative descriptive research, by examining various literatures and criticizing the problems that occur in the field. By sharing opinions, from the community, religious leaders and scholars that buying and selling gold by pre order is halal. Because basically dp (downpayment) is only used as a guarantee for the buyer's certainty to buy the gold. Not as a contract. Because the correct contract is when it is paid in full and the gold has been received at the price according to the day the gold is received. Gold here is categorized as jewelry according to the illatnya